A Conceptual Discourse on Consumer’s Preference of Brandy (Quest Journal of Management and Social Sciences, 2019)
Background: Liquor industry is growing to become a global giant by empowering its competitiveness. Nowadays, alcohol has been accepted and welcomed as a normal part of everyday life with innovatively embedded alcohol development and promotion. Alcohol products consist of a range of offerings including Gin, wine, vodka and Scotch, among which brandy has been gaining higher importance.Objectives: This paper explores the consumers’ preferences for brandy, their knowledge on brandy and also the factors determining the consumer choice on consumption of brandy.This study aims to contribute to the brandy consumer behavior-responsive managerial implications, especially in hospitality industry by identifying the attributes that are perceived important for the marketing of brandy to a large segment of dynamic market.Methods: The academic discourse on this paper includes exploration of multiple dimensions related to the study of consumer behavior. Theories concerning consumer preferences, with specific focus on Reasoned Action Theory, Engel Kollat Blackwell Model, Hybrid Choice Model, Hedonic Price Model, Consumer Perception Factor Model and Conjoint Analysis are reviewed.The study on brandy, along with the differences from other alcoholic beverages, has also been included.Findings: Brandy represents a wide category and the bases of differences among types of brandy are studied along with the review of brandy products available worldwide. This study highlights brandy consumption practices in the world, benefits of brandy consumption and people’s perception towards brandy among other alcoholic beverages.Conclusions: Alcohol is the fastest growing industry and requires consumer preference for the promotions and penetration of the product into the market, and for developingthe product and improving it further.